Learning Media Chatbot: Technology Innovation for Stunting Prevention - Sholihah, Umu; Sarwanto, Sarwanto; Sukmawati, Fatma (Universitas Sebelas Maret, 2023)
Stunting remains a global health issue at present. One important factor in preventing stunting is adequate nutrition from early stages. However, access to accurate and timely nutritional information continues to be a challenge, especially in remote and rural areas. In response, this qualitative study aimed to analyze the use of Chatbots as a facility for accessing nutritional information in an ef fort to prevent stunting. The data were collected through questionnaires and interviews. It involves 40 mothers with toddlers actively participating in the local integrated health posts (posyandu) as research subjects, selected specifically using purposive sampling. The data obtained from this research will be analyzed using the Miles and Huberman model. The research findings indicate that the current methods of delivering nutritional information, such as lectures and guidebook s, have limited impact in preventing stunting. Therefore, a chatbot emerges as a suitable medium for providing accessible nutritional information. This study contributes to addressing the global health issue of stunting and offers a potential technological solution to enhance access to nutritional information.